Phytochemical characterisation of an important medicinal plant, Chenopodium ambrosioides Linn. Issue 19 (2nd October 2017) - Shah, Hameed; Khan, Ashfaq Ahmad
Abstract: The project was intended to the phytochemical characterisation from the rudimentary methanolic extract of Chenopodium ambrosioides Linn., which escorts to the isolation of stigmasterol (1), β-sitosterol (2), octadecanoic acid (3), scopoletin (4) and 1-piperoylpiperidine (5). Literature validates the medicinal authentication of these compounds extorted from other sources, while our previous findings regarding microbial activities of different solvent systems fractions are favouring the presence of medicinally important compounds in this species. Herein, however, we report these natural products for the first time from this species. Abstract :